Prostaglandin F2α to induce farrowing in sows - Duane L Davis (Kansas Agricultural Experiment Station Research Reports, 1981)
Alternate groups of sows were synchronized, with prostaglandin, to farrow within a certain time or to serve as controls. The objective was to determine if baby-pig survival or litter-weaning weight would be improved by such group farrowing. Results indicated no improvement in those traits; therefore, if prostaglandin is used under the conditions of this experiment, its cost will have to be justified by other considerations.; Swine Day, Manhattan, KS, November 12, 1981
Keywords: Swine day; 1981; Kansas Agricultural Experiment Station contribution; no. 82-128-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 406; Swine; Prostaglandin; Farrowing; Sows